1993
DOI: 10.1007/bf01974071
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of several oximes on reactivation of soman-inhibited blood, brain and tissue cholinesterase activity in rats

Abstract: The ability of three oximes, HI-6, MMB-4 and ICD-467, to reactivate cholinesterase (ChE) inhibited by the organophosphorus compound soman was compared in blood (plasma and erythrocytes), brain regions (including spinal cord) and peripheral tissues of rats. Animals were intoxicated with soman (100 micrograms/kg, SC; equivalent to 0.9 x LD50 dose) and treated 1 min later with one of these oximes (100 or 200 mumol/kg, IM). Toxic sign scores and total tissue ChE activities were determined 30 min later. Soman marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…Although central nervous system effects are a major component of OP toxicity (Inns and Leadbeater, 1983;Shih, 1993;Wolthuis et al, 1994), classical oxime reactivators such as 2-PAM do not cross the blood-brain barrier (Bodor and Brewster, 1983). To determine whether ortho-7 or another bis-oxime might be superior in this respect, we treated rats with DFP, which, unlike echothiophate, readily inactivates brain AChE after systemic administration.…”
Section: Resultsmentioning
confidence: 99%
“…Although central nervous system effects are a major component of OP toxicity (Inns and Leadbeater, 1983;Shih, 1993;Wolthuis et al, 1994), classical oxime reactivators such as 2-PAM do not cross the blood-brain barrier (Bodor and Brewster, 1983). To determine whether ortho-7 or another bis-oxime might be superior in this respect, we treated rats with DFP, which, unlike echothiophate, readily inactivates brain AChE after systemic administration.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, numerous attempts had been made to improve the antidotal properties of the conventional mono-and bis-pyridinium mono(di)-oximes by modifying their structure as well as by the introduction of other heterocyclic systems, such as imidazolium, quinuclidinium, pyridinium-imidazolium, pyridinium-quinuclidinium, and quinuclidinium-imidazolium compounds. 26,[63][64][65][66][67][68][69] Additionally, recent experimental studies conducted with 1,1'-methylene-bis(4-(hydroxyimino)methyl) pyridinium dibromide (MMB-4) showed that, compared to HLö-7 and HI-6, MMB-4 was a less potent reactivator of AChE inhibited by sarin, several sarin analogues, soman, VX, VR or CVX. 3,70 Therefore, despite intensive research activities on this topic, PAM-2, TMB-4, LüH-6, HI-6 and HLö-7 have remained dominant among oximes in experimental work.…”
Section: Oxime Therapymentioning
confidence: 99%
“…Its deleterious effects are extraordinarily difficult to counteract due to the very rapid aging of soman-inhibited AChE (2,6). In addition, the main action of soman is in the central nervous system where the reactivating efficacy of all oximes is low owing to their limited penetration through blood-brain barrier (7)(8).…”
Section: Introductionmentioning
confidence: 99%